Empleo del tiempo libre, las actividades físicas y recreativas en los niños del barrio el calvario de la ciudad de Catacocha cantón paltas. - Agila Agila, Oswaldo Vicente (2016)
This research work called somatotipológicas study of characteristics and physical tests on athletes Stayers Sports Federation Loja, a general objective was established; Determine whether the study of somatotipológicas characteristics and physical tests on athletes Stayers, Loja Sports Federation morpho improves the physiological response during training. To deepen the theory of our research, we rely on the literature review of different authors, which allowed us the development of the theoretical framework, they are treated categories related to the valuation of an athlete, kinanthropometry, somatotype, physical tests, athletics: Stayers. The methodology involves a qualitative approach was applied, with a descriptive character, the temporal dimension of the research is a longitudinal study, the design is experimental pre, which was developed with a single group, performing a pretest and posttest, also determining the initial and final characteristic of this type of design somatotype. anthropometric, inductive method was applied - deductive, to know the real situation of morphological and physical conditions in athletes investigated. techniques and instruments such as a survey that allowed diagnose the problem, personnel files, payroll data collection were a great help to obtain the necessary data for the research was conducted. Reaching the results that the dominant somatotype 60% of the athletes is ectoendomorph, and physical test results 80% of athletes with excellent performance. The author concludes that compliance was given to the proposed objectives since it was implemented and evaluated alternative as recommendation given is generalized to other sports this alternative: the proposal anthropometric measurements and physical tests on athletes Stayers in Sports Federation Loja.